C. elegans Methods and Applications - Biron, David; Haspel, Gal.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
The aim of this volume is to provide a step-by-step guide for implementing a selection of novel techniques in the lab. Each protocol in this volume is presented as a standalone chapter, specifically geared towards addressing practical needs without presuming prior knowledge of the technique at hand. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, C. elegans: Methods and Applications, Second Edition aims to ensure successful results in the further study of this dynamic field.
Library Construction for Mutation Identification by Whole-Genome Sequencing -- Fundamentals of Comparative Genome Analysis in Caenorhabditis Nematodes -- Genetic Methods for Cellular Manipulations in C. elegans -- A Fusion PCR Method for Expressing Genetic Tools in C. elegans -- Transposon Assisted Genetic Engineering with Mos1 Mediated Single-copy Insertion (MosSCI) -- Creating Genome Modifications in C. elegans using the CRISPR/Cas9 System -- Observing and Quantifying Fluorescent Reporters -- Microbial Rhodopsin Optogenetic Tools: Application for Analyses of Synaptic Transmission and of Neuronal Network Activity in Behavior -- Simultaneous Optogenetic Stimulation of Individual Pharyngeal Neurons and Monitoring of Feeding Behavior in Intact C. elegans -- High-Pressure Freeze and Freeze Substitution Electron Microscopy in C. elegans -- Electron Tomography Methods for C. elegans -- Microfluidic Devices for Behavioral Analysis, Microscopy, and Neuronal Imaging in Caenorhabditis elegans -- Tracking Single C. elegans using a USB Microscope on a Motorized Stage -- An Imaging System for C. elegans Behavior -- A Method for Obtaining Large Populations of Synchronized Caenorhabditis elegans dauer Larvae -- Sampling and Isolation of C. elegans from the Natural Habitat -- A Primer on Prototyping -- A Primer on Quantitative Modeling.
Keywords: Human genetics; Animal genetics; Animal models in research; Human Genetics; Animal Genetics and Genomics; Animal Models